การใช้ซีรั่มแลคเตทจากเลือดแดงขณะแรกรับในโรงพยาบาลเป็นตัวทำนายการเกิดภาวะแทรกซ้อนรุนแรงของผู้ป่วยกล้ามเนื้อหัวใจตายเฉียบพลันที่ได้รับการใช้สายสวนหลอดเลือดหัวใจพร้อมกับการรักษาด้วยการขยายหลอดเลือดด้วยบอลลูน - วรวรรณ เจริญอัตถะศีล (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
BACKGROUND: Primary percutaneous coronary intervention (PCI) appears to be the preferred reperfusion method for patients with ST-segment elevation myocardial infarction (STEMI) but after successful reperfusion there are some patients had poor outcomes. From previous study, the risk factors were old age, female, Killip’s class IV, multivessel disease and LVEF < 40%. Little is known about the clinical correlates of arterial serum lactate in patients with ST-segment elevation myocardial infarction (STEMI).OBJECTIVE: To determine the arterial serum lactate was a predictor for in-hospital major adverse cardiac events (MACE); death, re-infarction, shock, heart failure and 30 day mortality in acute myocardial infarction patients who treated with primary percutaneous coronary intervention (PCI).METHODS: The prospective cohort single-center study at King Chulalongkorn MemorialHospital enrolled 72 STEMI patients who treated with primary percutaneous coronary intervention (PCI) between 1 January 2013 and 31 October 2013 (10 months) analyses arterial serum lactate, clinical characteristics, angiographic feature, in-hospital outcomes and 30 day mortality.RESULTS: Fifty-five consecutive patients with STEMI were included in the study. The baseline characteristic the mean age was 56 ± 14 years and 11% were older than 75 years old. Fifty-eight percent of patients were referred from non-PCI capable hospital. There were 16.7 % of patients with left ventricular ejection fraction less than 40% and 27.3% of patients with Killip’s class IV. About half of the patients had multi-vessels disease. The overall angiographic success rate was 96.4%.During hospitalization, in-hospital mortality rate was 12.7% and MACE rate (death, re-infarction, cardiogenic shock and heart failure) was 34.5 %. The mean arterial serum lactate at admission was significant different in MACE group compare with no MACE group (5.88 vs 1.55 mmol/L, p<0.001). Patients who had LVEF below 40% or multi-vessels disease were significant factors that effect in-hospital MACE (p = 0.006, p = 0.023, respectively). There were no significant different in in-hospital MACE after classified by age and sex (p = 0.947, p = 0.73, respectively).After adjusted by Age, Gender, LVEF < 40% and Multi-vessels disease, Lactate and Killip’s class were the predictors for in-hospital MACE (adjusted OR = 9.9; 95%CI = [1.4-69.4] and 11.4 ; 95%CI = [2.5 - 51.6], respectively). The 30 days mortality rate after discharge was 3.9%, there was no significant different of mean arterial serum lactate in both groups (p = 0.841).By ROC curve, a cutoff value of arterial serum lactate 1.85 mmol/L to in-hospital MACE, the sensitivity, specificity, positive predictive value and negative predictive value were 100%, 77.8%, 70.4% and 100% respectively.CONCLUSIONS: In STEMI patients, higher lactate levels was related with in-hospital MACE but not related with 30 day mortality. Point-of-care measurement of arterial lactate at admission in patients with STEMI has the potential to improve immediate risk stratification in these patients.